Digital Marketing Strategy on Fashion Industry among Z Generation in Batam City - Susanti, Tri; Siahaan, Mangapul (Politeknik Negeri Batam, 2022)
The Internet has become a part of society in almost all areas of business. The popularity of the internet causes increase in the needs of the community, especially generation z which has a major influence on daily life. Information that is spread through social networks is a solution to the needs of generation z. They can make purchases online by utilizing digital media and available information. This study was conducted to determine the effect of digital marketing on online purchase intention of generation z in Batam City in the fashion industry through brand equity and consumer perceived value. This study uses an explanatory sequential mixed method that combines both quantitative and qualitative methods. Data collection on the quantitative method was carried out by distributing questionnaires to 404 respondents and analyzed by using the Structural Equation Modeling (SEM) using SPSS Statistics 25 and SPSS AMOS 22. The qualitative method was carried out by interviewing 20 sources and analyzed by classifying the data used to support quantitative results. This study shows that digital marketing does not have a positive effect on online purchase intentions, digital marketing does not have a positive effect on online purchase intentions through brand equity as a mediator, and digital marketing has a positive effect on online purchase intentions through consumer perceived value as a mediator.